The Oxford handbook of public choice. Volume 2 - Congleton, Roger D.; Grofman, Bernard; Voigt, Stefan (New York : Oxford University Press, 2019)
The two volume Oxford Handbook of Public Choice provides a comprehensive overview of the Public Choice literature. Volume 2 covers constitutional political economy and applications of public-choice models to various policy areas. Part V has chapters on the architecture of governance, the theory of dictatorship, and the effects of the institutions of governance. Part VI discusses the politics of public policy, international public choice, public choice and history, and measurement issues. The volume touches on topics such as taxation, redistribution, federalism, and monetary policy. It ends with discussions of various methodological approaches, including extensions of the core models to account for altruism and trust, and overviews of measurement and estimation issues, and the use of experiments in public-choice research.
How should votes be cast and counted? / Nicolaus Tideman -- Choosing voting rules in the European Union / Běla Plechanovová, Madeleine O. Hosli, Anatolij Plechanov -- Leviathan, taxation, and public goods / Martin C. Mcguire -- Fiscal powers revisited: the Leviathan Model after 40 years / Geoffrey Brennan, Hartmut Kliemt -- Are There Types of Dictatorship? / Ronald Wintrobe -- Are there really dictatorships? The Selectorate and authoritarian governance / Alejandro Quiroz Flores -- The coup: competition for offices in authoritarian regimes / Toke Aidt, Gabriel Leon -- The logic of revoluions: Rational choice perspectives / Timur Kuran, Diego Romero -- Direct democracy and public policy / John Matsusaka -- Policy differences among parliamentary and presidential systems / Sebastian M. Saiegh -- The significance of political parties / Michael Munger -- Voters and representatives: How should representatives be selected? / Thomas Braendle, Alois Stutzer -- The least dangerous branch? Public choice, constitutional courts, and democratic governance / Georg Vanberg -- Challenges in Estimating the Effects of Constitutional Design on Public Policy / Stefan Voigt, Jerg Gutmann -- The Political Economy of Taxation: Power, Structure, Redistribution / Stanley L. Winer -- The politics of central bank independence / Jakob DeHaan, Sylvester Eijffinger -- The Political Economy of Redistribution Policy / Luna Bellani, Heinrich Ursprung -- Political participation and the welfare state / Rainald Borck -- Institutions for Solving Commons Problems: Lessons and Implications for Institutional Design / Paul Dragos Aligica, Michael E. Cox -- Rational Ignorance and Public Choice / Ilya Somin -- Divided government: the king and the council / George Tridimas -- Is government growth inevitable? / Randall G. Holcombe -- The political economy of international organizations / Axel Dreher, Valentin F. L
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 5, 2019).
Keywords: Social choice